Benzodiazepines and Geriatrics: What Clinical Practice Strategies Can Be Used to Reduce the Inappropriate Prescribing?. Issue 5 (September 2016) - Gregg, Jason A.; Tyson, Ronald L.; Cook, Donna
Abstract : Abstract: In the elderly, Potentially Inappropriate Prescriptions (PIPs) are quite common and connected with adverse drug events (ADEs), hospital stays, increased medical acuities, and inefficacious healthcare. Benzodiazepines as a class have been identified as an independent risk factor for ADE's and shown to be associated with sedation and impairments in cognition, memory, and balance, lending to an increased risk for falls. Clinically inappropriate medications continue to be prescribed and preferred by many clinicians over non‐pharmacological strategies despite continued evidence demonstrating poor outcomes in older adults. Due to the increasing evidence in positive elderly outcomes through the reduction in use of inappropriate drugs, medication reduction strategies are now required policy components in the Centers for Medicare and Medicaid Services regulations along with Medicare Part D. Quality measures now focus on extensive drug reviews with reduction strategies that incorporate use of: the Beers Criteria; multidisciplinary approaches; involving patients and caregivers; and de‐prescribing strategies.